Extended nonlinear parametric process in anomalously pumped linear cavity oscillator - Lim, L. T.; Yeo, Kwok Shien; Abu Bakar, Muhammad Hafiz; Tamchek, Nizam; Mahdi, Mohd Adzir (Optical Society of America, 2014)
We demonstrate a linear cavity fiber optical parametric oscillator with extended pump-signal separation of 14.3 THz (116 nm). The signal laser is provided by a pair of 1675nm fiber Bragg gratings and a tunable idler from 1456.12 nm to 1462.48 nm is generated by detuning the pump wavelength in the anomalous dispersion regime of a highly nonlinear fiber. At such large pump-signal separation, we are still able to record a parametric conversion efficiency of more than −35 dB and idler optical signal-to-noise-ratio of 50 dB on average. The stability of the lasing signal and idler is examined and result shows both signal and idler peak power fluctuation is less than 1 dB over a period of 30 minutes.